2019
DOI: 10.5194/nhess-2019-116
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Revised earthquake sources along Manila Trench for tsunami hazard assessment in the South China Sea

Abstract: Abstract. Seismogenic tsunami hazard assessments are highly dependent on the reliability of earthquake source models. Here in a study of the Manila subduction zone (MSZ) system, we combine the geological characteristics of the subducting plate, the geometry, and coupling state of the subduction interface to propose a series of fault rupture scenarios. We divide the subduction zone into three rupture segments: 14° N–16° N, 16° N–19° N and 19° N–21.7° N inferred from geological structures associated with the dow… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 67 publications
(171 reference statements)
0
3
0
Order By: Relevance
“…(2016) showed that the occurrence of great earthquakes of M w 8.8–9.2 in the Manila Trench is plausible. It was further supported by (Qiu et al., 2019) that the Manila Trench is capable of generating M w 8.5+ earthquakes with a return period of 1,000 years.…”
Section: Potential Seismic Sourcesmentioning
confidence: 79%
“…(2016) showed that the occurrence of great earthquakes of M w 8.8–9.2 in the Manila Trench is plausible. It was further supported by (Qiu et al., 2019) that the Manila Trench is capable of generating M w 8.5+ earthquakes with a return period of 1,000 years.…”
Section: Potential Seismic Sourcesmentioning
confidence: 79%
“…However, the chances of preserving tsunami deposits greatly decrease due to intense human activities, for example, land reclamation, urban development in coastlines of the mainland. So far, all the sites which have reported geological evidence of possible tsunamis in SCS are located in relatively remote islands (Qiu et al, ), including Dongdao Island (Sun et al, ), Yongshu Island (Yu et al, ), Badoc Island near Luzon (Ramos et al, ) and Nanao Island in southern Chinese coastline (Yang et al, ). Based on the combined information of numerical results, geological setting and the available geological studies, we would suggest that the islands located in the offshore area of southern China have the highest chance for such evidence being found.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the bathymetry on the eastern and western sides alongshore, the seafloor bathymetry perpendicular to the coastline in front of the PRE is relatively high, which forms a hump, slows down wave propagation and leads to shoaling of the tsunami waves. (5) In terms of tsunami arrival time, when comparing with the tsunami waves generated by megathrust earthquakes from the Manila subduction zone (Qiu et al, ), tsunami waves generated by the studied landslides arrive ~1 hr earlier at coastlines in southern China and central Vietnam and ~0.5 hr later at coastlines in Taiwan and Philippines. (6) Nonlinearity has a considerable effect on the coasts with wide continental shelf, especially in front of the PRE region, and has negligible effect on coasts with a narrow continental shelf, for instance, western Philippines, central Vietnam, and Southern Taiwan.…”
Section: Discussionmentioning
confidence: 99%